(untitled) (International Journal of Engineering and Computer Science, 2014)
A large number of temporary nodes consisting of set of rules and destination based services require that mobile nodes learn the nearest places. A process can be easily improper usage or interrupt by opposition nodes. In being away of fixed nodes the discover and verifying of nearest places that have been hardly inquired in the existing system .In this thesis by introducing a complete distributed answer that is strong and secret against adjacent nodes and can be damaged only by an huge number of neighbor nodes . Results that a set of rules can occur more than 99 percent of the threats . under the best possible state the original nodes are to be searched